PERANCANGAN WEBSITE INFORMASI DAN PROMOSI DESA MENGGUNAKAN METODE EXTREME PROGRAMMING PADA DESA SIMPANG TUNGKAL - M. Leo Irpan; Novri Hadinata; Muhamad Ariandi (P3M Institut Teknologi Pagar Alam, 2023)
The use of information technology at this time has developed very quickly, becoming more widespread along with the increasing need for information, but currently the Simpang Tungkal Village Office has not yet fully used information technology, at a time when the dissemination of information relating to the village is still very limited and still less effective. resulting in the accuracy of the information received by the public being invalid. To overcome this, a village information website system is needed which will provide solutions to these problems. So a village information website was designed which was built using the Extreme Programming (XP) method which in implementing the design was more effective and efficient, by utilizing system design using UML (Unified Modeling Language), and testing the system using Black Box Testing to find out whether the user interface was correct. works fine. So this research produces a village information website which contains information related to Simpang Tungkal village, which is a medium for publishing village information and also a media for promoting village products.